PRODUCTIVITY OF GRAIN CROPS AND SOIL FERTILITY DEPENDING ON FERTILIZERS, TYPE OF SOIL IN THE SYSTEM OF CROP ROTATION - I. N. Romanova; S. M. Knyazeva; S. N. Glushakov; S. E. Terentiev; М. I. Perepichay (Зерновое хозяйство России)
Introduction of innovative technologies and crop rotation is agrotechnological and ecological basis for productivity growth and stability. Due to the proper crop rotation in the soil the amount of organic matter increases, the nutritional elements accumulate, biologic processes become active and all these increase productivity and quality of the product in 1.5-2 times. The article has presented the study results of the effect of crop rotation, type of soil, use of fertilizers on productivity of grain crops and change of the elements of soil fertility in the western part of the Central Russia. The trials have been conducted at the experimental field of Smolensk Agricultural Academy on the sod-strongly-podzolic and medium-podzolic medium-loamy soils with the six crop rotation sequences (cropped fallow, winter grain crops, spring grain crops, lupine, potato, spring grain crops). The crop rotation was started in 1992, from that time there has been four rotation sequences. The initial material consisted of new and promising varieties of grain crops, approved to use in the Central Russia. The agro machinery was conventional for the area (nechernozemnaya zone). All the researches were done according to the conventional methods and GOSTs. Agroclimatic conditions of the years differed in the temperature regimes and the amount of precipitations, that allowed estimating the effect of the agro methods on soil fertility and productivity of grain crops. The researches of the years 1992-2015 showed that four crop rotation sequences on the sod-strongly-podzolic and sod-medium-podzolic medium-loamy soils without the use of fertilizers increased the contents of humus on 0.17%, readily  hydrolysable nitrogen on 21 mg/kg, available phosphorus on 37 mg/kg, exchangeable potassium on 28 mg/ha; when the fertilizers were used the contents of these element increased on 0.32%, 20 mg/kg, 40 mg/kg, 74 mg/kg of soil respectively. On average the productivity of the grain crops on the sod-medium-podzolic soil was 4.76 t/ha, which excessed the productivity on the sod-strongly-podzolic soil on 0.74 t/ha. The application of the fertilizers in the crop rotation increased the productivity of the crops on 2.67 t/ha.